Kingdom of Morocco : Promoting Youth Opportunities and Participation - World Bank (Washington, DC, 2012)
This policy note, based on the Morocco Household and Youth Survey (2009-10), analyzes the aspirations of young Moroccans aged 15 to 29 years, their economic and social circumstances, as well as the institutional factors that hinder their economic and social inclusion. This study adopts a mixed method approach combining an innovative quantitative instrument with qualitative and institutional analysis. The goal is to provide policy makers with a nuanced analysis of barriers to employment and active civic participation that youth face, in order to come up with more effective youth interventions. A wide range of recommendations is identified to support youth inclusive activities and policies, and a roadmap for integrated youth investments. The study reviewed institutions and programs that offer diverse services to young people, including: employment, training opportunities, community participation, summer camps, sports, and recreational activities, which form the foundation for a comprehensive youth program in Morocco. An integrated package of measures aimed at both improving existing services and offering new ones to cover current gaps, is urgently needed to address youth demands for meaningful social and economic inclusion. The report recommends focusing in particular on two key areas: (i) promoting employability, linkages to the labor markets and entrepreneurship and (ii) active youth participation. It concludes by offering recommendations for youth inclusive policies and a plan of integrated youth investments which could expand the scope of employment and participation opportunities currently available.